Propuesta operativa para la implementación y consolidación de un sistema de análisis y monitoreo del riesgo de extinción de la fauna silvestre en Colombia (2016)
The quantification and classification of the risk of extinction for a species within a country or region and the publication of red list are fundamental tools for preventing and managing the loss of biodiversity on a sub-global scale of anthropogenic activity. Colombia may be considered a regional leader in the development of this type of risk analysis (i.e. red books published in 2002 and recent re evaluations of birds and freshwater fish); however, there are many challenges to increasing taxonomic coverage, periodic assessments, sustainability and also the influence on conservation planning and management in Colombia. This working paper presents a proposal to create, implement and consolidate an -Operative System for Risk Extinction Analysis and Monitoring of the Colombian Wildlife to address more effectively the challenges outlined above. It originates from research that identified progress and gaps on this issue in Colombia in relation to other countries of the world and also from discussions and recommendations by South America fauna experts. Based on these elements, the proposal presents objectives, guidelines, instances, roles, activities and work schemes that should be considered relevant to increase the rigor, transparency, periodicity, sustainability and impact of the wildlife risk assessments in Colombia. The system here presented is preliminary and should be amply consulted and discussed in order to make the necessary adjustments to obtain a definite working model for Colombia.